2023
DOI: 10.3390/molecules28217388
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and AMPK: A Dynamic Duo in Alleviating MG-Induced Inflammation via the AMPK/SIRT1/NF-κB Pathway

Ziyin Lu,
Haozhen Wang,
Muhammad Ishfaq
et al.

Abstract: Mycoplasma gallisepticum (MG) is recognized as a principal causative agent of avian chronic respiratory disease, inflicting substantial economic losses upon the poultry industry. However, the extensive use of conventional antibiotics has resulted in the emergence of drug resistance and various challenges in their clinical application. Consequently, there is an urgent need to identify effective therapeutic agents for the prevention and treatment of mycoplasma-induced respiratory disease in avian species. AMP-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Additionally, a reduction in Il-6, Il-1β, and TNF-α release was shown in LPS-stimulated human gingival fibroblasts [ 69 ]. Lu et al [ 70 ] showed that quercetin effectively inhibited the secretion of pro-inflammatory cytokines such as Il-1β, TNF-α, and Il-6 in Mycoplasma gallisepticum chronic avian respiratory disease and increased the levels of phosphorylated AMPK and SIRT1 while reducing the levels of phosphorylated P65.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a reduction in Il-6, Il-1β, and TNF-α release was shown in LPS-stimulated human gingival fibroblasts [ 69 ]. Lu et al [ 70 ] showed that quercetin effectively inhibited the secretion of pro-inflammatory cytokines such as Il-1β, TNF-α, and Il-6 in Mycoplasma gallisepticum chronic avian respiratory disease and increased the levels of phosphorylated AMPK and SIRT1 while reducing the levels of phosphorylated P65.…”
Section: Discussionmentioning
confidence: 99%